(3HOGjI GdShd ajeG SfM ef JaVjd GdQShds - (3YR GdOjf YHO GdYRjR Hf YHO GdSdGe Hf CHh GdbGSe Hf GdMSf GdSdej GdOeTbj, GdYR Hf YHO GdSdGe,J (B660 (3g` s ((3eMeO Hf eMeO Hf efUhQ GdMSjfj s)
(3ChdgG (B:s
(3bGd Gddg JYGdi dfHjfG UdhGJ Gddg hSdGeg Ydjg eeJfG Ydjg , eYQaG dbOQI hdOjg (B"(3hGfRd Ydjc GdcJGH hGdMceI hYdec eGde Jcf JYde hcGf aVd Gddg Ydjc YXjeG(B" s
(3BNQgG (B:s
(3hgPg deY hETGQGJ jcJai GdYGbd GdaWf HeKdgG Hd HHYVgG s
(3Vef eLehY s
(3GfXQ HQbe (B79 (3JGQjNs
(3HChdgG SfO QhGjI GdcJGH Yf eDdags
(3hHBNQgG bQGAGJs
(3fSNI KGdKI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdJGQjNs